2009
DOI: 10.1007/s11101-009-9124-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity of the bioactive compound inositol pentakisphosphate

Abstract: Bioactive compounds are extra nutritional constituents found in small quantities in foods. We have recently shown that a bioactive compound, inositol pentakisphosphate (IP 5 ), a naturally occurring substance that is present in most legumes, wheat bran and nuts, inhibits cell growth of ovarian, lung and breast cancer cells. We demonstrated that IP 5 specifically blocks the activation of the critical phosphoinositide 3-kinase (PI3K) effector Akt, a serine/threonine kinase which plays a key role in different int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition, the effect of such high accumulation of IP 5 and IP 4 will need to be evaluated for nutritional value in soybean meal. Interestingly, a series of studies identified IP 5 as a potential anticancer compound because it can block the activation of a critical human enzyme which plays a key role in cell survival and proliferation (reviewed in Falasca, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effect of such high accumulation of IP 5 and IP 4 will need to be evaluated for nutritional value in soybean meal. Interestingly, a series of studies identified IP 5 as a potential anticancer compound because it can block the activation of a critical human enzyme which plays a key role in cell survival and proliferation (reviewed in Falasca, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In some in vitro studies IP 6 has been demonstrated to stop breast cancer cell proliferation in human cell lines (107). Another very interesting bioactive compound present in wheat bran, legumes and nuts at very high concentration (108), is IP 5 . It has been recently proved that this substance plays a role as anti-tumor agent in mice and that it enhances the effect of cytotoxic drugs in ovarian and cancer cells (69)(70)(71)108).…”
Section: Experimental Studiesmentioning
confidence: 99%